The Relationship Of The Implementation Of Character Education In Family And The Social Behavior Of Adolescents - Lyvia Agustin; Wisroni Wisroni (Universitas Negeri Padang, 2022)
The background of this research is the low social behavior of adolescents in Nagari Lunang 2, Lunang District, Pesisir Selatan Regency, which is thought to be caused by the application of character education in the family which is still low. This study aims to describe the social behavior of adolescents, describe the application of character education in the family, and see the relationship between the application of character education in the family and the social behavior of adolescents in Nagari Lunang 2. This research is a quantitative correlational type. The population in this study were all teenagers who were of junior high school and high school education age. Sampling using area random sampling technique. Data collection techniques using a questionnaire or questionnaire. The data obtained were analyzed using descriptive analysis and product moment correlation. The results of this study indicate that the application of character education in the family is low, the social behavior of adolescents is not good, and there is a significant relationship between character education in the family and the social behavior of adolescents in Nagari Lunang 2. Research suggestions are suggested to parents and the community to increase their role in the application of character education to children in the family environment, and it is recommended for family empowerment institutions to decide a policy, especially in order to improve the ability of parents to implement character education in the family. Keywords: character education, social behavior, family education